Interaction of guided waves with delaminations in composite plate structures - Gupta, Saurabh (2017)
This paper addresses a gap in the literature on the 3-dimensional scattering of the fundamental symmetric Lamb mode S0 from delimitations in composite plates. We study the scattering of low-frequency S0 Lamb mode from a delamination in a stiffened 4-ply CFRP composite plate with [0/0]S ply orientation. Far field scattering coefficients for the S0 Lamb mode are plotted as a function of circumferential position around the delamination using 3D FE simulations. Results show that the delamination size has less influence on S0 Lamb wave scattering in the low-frequency regime where the S0 mode is non-dispersive. Further analysis was done using two-dimensional FE simulation for different ply-layup orientations with S0 Lamb mode. This study shows that ply-layup orientation and through-thickness delamination location in fiber composite laminate have a significant influence on S0 Lamb mode interaction. We also analyzed the interaction of A0 Lamb mode for a few cases. This work will be useful for practical Lamb wave based inspection of composite plate structures.